In Situ AFM and Electrochemical Study of a Waterborne Acrylic Composite Coating with CeO2 Nanoparticles for Corrosion Protection of Carbon Steel. Issue 10 (19th August 2015) - Li, Jing; Ecco, Luiz; Ahniyaz, Anwar; Fedel, Michele; Pan, Jinshan
Abstract : The corrosion protection of a waterborne acrylic composite coating with 1 wt% ceria nanoparticles (CeNP) coated on carbon steel in 3 wt% NaCl solution was investigated by ex-situ and in situ as well as electrochemical atomic force microscopy (AFM) observations, combined with open circuit potential (OCP) and electrochemical impedance spectroscopy (EIS) measurements. The synthesized CeNP were stabilized by acetic acid. The transmission electron microscopy characterization showed fine nano-size of as-synthesized CeNP, the ex-situ AFM imaging revealed uniform dispersion of the CeNP in the composite coating and greatly reduced nano-sized pinholes in the coating. The in situ and electrochemical (EC) AFM investigations indicate release of some CeNP and aggregates from the coating surface and then precipitation of some particles and cerium-compounds during the exposure. The OCP and EIS results demonstrated that the addition of 1 wt% CeNP leads to a significantly improved long term barrier type corrosion protection of the waterborne acrylic composite coating for carbon steel in 3 wt% NaCl solution. The beneficial effect of the CeNP is attributed to the blocking of nano-sized defects and inhibition by the cerium compounds originated from the acetic acid stabilized CeNP.